Development of Communicative-Rhetorical Competence of a Future Engineer at the Research University - F. T. Shageeva; M. L. Smirnova (Высшее образование в России, 2019)
The article focuses on the development of the communicative-rhetorical competence of a future engineer. This competence is considered to be a necessary condition for his development as a qualified specialist and a significant factor in his/her future professional activities. In the XXI century, in modern conditions, engineering and engineering duties should be inseparable from organizational and managerial activities. The solution of production problems and team work with diversified specialists are realized through communicative and rhetorical qualities of an engineer. He/ she should be ready for productive business communication and effective presentation of his/her position, as well as presentation of the results of work. Public speaking skills hence acquire particular importance for engineers along with communication skills. Communicative-rhetorical competence is the ability to carry out a conscious effective speech influence in the process of interpersonal, group and collective public communication, which measure up linguistic and cultural norms, and realizes the goals of communication through the use of various language levels. It is advisable to develop communicative-rhetorical competence of future engineers at the level of university training. The rationale for its effective development is proposed by creating a set of relevant pedagogical conditions: the introduction of an additional discipline “Rhetoric” or the modernization of an existing subject program with a similar focus; using of special educational technologies and methods for the development of communicative-rhetorical competence; advanced training of university teachers; creation by the university of appropriate conditions for active research and social activities of students; cooperation of educational institutions with large enterprises, companies and research centers. The pedagogical conditions should take into account the capabilities of a research university: the integrated nature of the learning process; using modern educational technologies in the process of learning; availability of a developed system of professional retraining and advanced training of teachers and other specialists. The authors worked out the recommendations for the selection and structuring of the material, as well as methods for developing the communicative and rhetorical competence of future engineers in a research university, and also identified problems that need further consideration, including the search for innovative techniques and methods.